Neocortical Inhibitory Terminals Innervate Dendritic Spines Targeted by Thalamocortical Afferents - Kubota, Yoshiyuki (J Neurosci, 2007)
Fast inhibition in the cortex is gated primarily at GABAergic synapses formed by local interneurons onto postsynaptic targets. Although GABAergic inputs to the somata and axon initial segments of neocortical pyramidal neurons are associated with direct inhibition of action potential generation, the role of GABAergic inputs to distal dendritic segments, including spines, is less well characterized. Because a significant proportion of inhibitory input occurs on distal dendrites and spines, it will be important to determine whether these GABAergic synapses are formed selectively by certain classes of presynaptic cells onto specific postsynaptic elements. By electron microscopic observations of synapses formed by different subtypes of nonpyramidal cells, we found that a surprisingly large fraction (33.4 ± 9.3%) of terminals formed symmetrical synaptic junctions onto a subset of cortical spines that were mostly coinnervated by an asymmetrical terminal. Using VGLUT1 and VGLUT2 isoform of the glutamate vesicular transporter immunohistochemistry, we found that the double-innervated spines selectively received thalamocortical afferents expressing the VGLUT2 but almost never intracortical inputs expressing the VGLUT1. When comparing the volumes of differentially innervated spines and their synaptic junction areas, we found that spines innervated by VGLUT2-positive terminal were significantly larger than spines innervated by VGLUT1-positive terminal and that these spines had larger, and more often perforated, synapses than those of spines innervated by VGLUT1-positive afferent. These results demonstrate that inhibitory inputs to pyramidal cell spines may preferentially reduce thalamocortical rather than intracortical synaptic transmission and are therefore positioned to selectively gate extracortical information.